FEMALE INFERTILITY ASSOCIATED WITH GENITAL TUBERCULOSIS - T. V. Klinyshkova; A. A. Yakovleva (Акушерство, гинекология и репродукция, 2018)
Analysis of the published reports indicates the alarming increase in prevalence of infertility that occurs in the current demographic situation and the unfavorable epidemiological trends in tuberculosis. At present, female genital tuberculosis (GT) is considered the cause of 10-27.8% of female infertility cases and seen as a serious medical and social problem in women of reproductive age (24-35 years). Making a diagnosis of GT may become a complex task since: there are no commonly accepted schemes for the diagnostic procedure and patient management; the clinical manifestations of GT are nonspecific; the molecular-genetic, morphological, and microbiological diagnostic methods may not be sufficiently sensitive; the results of using hysterosalpingography are inconsistent (40-60% of discrepancies, high risk of complications); the indications to the Koch test and test-therapy are limited; the use of laparoscopy is still debatable; and the heterogeneity of the endoscopic picture in 13-59.7%  of suspected GT cases results in a low rate of confirmed GT – 9-26.3%. Immunological methods, in particular, the serological ones, take a lead in the diagnosis of extra-pulmonary tuberculosis. We propose that testing the local humoral immunity in women with infertility, along with the endoscopy, can improve the diagnosis of GT and avoid irreversible changes in the reproductive system.